The effect of using the team quiz method on student learning outcomes in mathematics subjects - Wakhidatul fitriah; Agus Setiawan; Saidun Anwar; Fitroh Ariansyah; Manteena Madhavi (CV. Bimbimbingan Belajar Assyfa, 2023)
The team quiz learning method is tested to see if it improves math learning for Mts Tri Bakti Al-Ikhlas Seputih Agung pupils. This research uses quantitative quasi-experimental methods. This study included Mts Tri Bakti Al-Ikhlas Seputih Agung class VII pupils. For this study, class VIIA was experimental, and class VIIB was control. The practical and control classes each have 20 students. Students took multiple-choice pretests and posttests in this study. This study processed data using normality, homogeneity, and t-tests. Data processing showed that the experimental class posttest> control class posttest (0.539> 0.149), indicating that the team quiz learning method had an impact on class VII mathematics learning at Mts Tri Bakti Al-Sincere Bumi Mas Seputih Agung.